EKSENTRISITAS DIGRAF PADA GRAF GIR MENGGUNAKAN ALGORITMA BREADTH FIRST SEARCH - Romario Marselino Barahama; Chriestie E.J.C. Montolalu; Rinancy Tumilaar (Sam Ratulangi University, 2021)
Let be a graph with the set of points and the set of sides . The distance from point u to v in is the length of shortest path from point to , denoted by . The eccentricity of point in graph is the furthest distance from point to each in denoted by . The point is the eccentic point of if . The purpose of this research is determine the eccentricity of the digraph on the gear graph and determine the eccentricity of the digraph gear graph using the breadth first search algorithm. The method used is to collect library sources in the form of books other refrences ehich are then used as the basis for conducting this research. Based on the discussion it can be concluded that the sahpe of eccentricity of the digraph on graph is complete symetry with Graph Theory is the one of the math theory with mathematic knowledge using with , and , while for the eccentricity the digraph on the digraph gear uses breadth first search algorithm is , and .